Analisis Investasi Pengadaan Alat Gali Muat dan Alat Angkut PT. Benal Aiti Bara Perkasa Kecamatan Mandiangin Kabupaten Sarolangun Provinsi Jambi - Fakhri Afif Rifa'i; Heri Prabowo (Departemen Teknik Pertambangan FT UNP, 2021)
This research is based on the company's planning for the procurement of digging and loading equipment and transportation equipment. The unit requirements planned by PT. Benal Aiti Bara Perkasa is 2 fleets and the Match Factor calculation is based on 2 operating fleetsIn this research, the method used is descriptive quantitative research method. This research will result in the compatibility of loading and unloading equipment and a comparison of the alternative of buying and renting units.Based on the results of the study, it shows that the equipment compatibility has not been achieved on the operating fleet. Based on his calculations, it can be seen that the unit requirements to achieve the Match Factor are 1 Excavator and 8 Dump Trucks. Alternative purchases and leases will provide existing investment components such as equipment procurement costs, operating costs and fixed costs that will affect the feasibility of investments such as Net Present Value (NVP) and Internal Rate of Return (IRR). The alternative purchase resulted in an NPV of Rp. 53,210,015,722, an IRR of 53.3% and a PI of 2.42. While the alternative rental NPV generated is Rp.29,090,911,882, IRR is 39.2% and PI is 1.82. The purchase alternative is the best choice than the rental alternative, because it gets a bigger profit. Keywords: Match Factor, Descriptive Quantitative, NPV, IRR and PI